Introducing food science - Shewfelt, Robert L. (Boca Raton : CRC Press, 2009)
Addresses a range of food issues facing today's consumer, proceeding from a general and student-friendly discussion to an in-depth technical overview of the basic principles of food science. This authoritative textbook starts by addressing food issues in the news, from disease outbreaks to the health benefits and detriments associated with international trade. It then outlines the basic principles of food manufacturing and processing techniques with a strong emphasis on unit operations.--COVER.
Food safety -- Healthiness of foods -- Choosing the food we eat -- Processed foods -- Formulated foods -- Chilled and prepared foods -- Quality assurance -- Product and process development -- Government regulation and basic research -- Food chemistry -- Nutrition -- Food microbiology and biological properties of foods -- Food engineering -- Sensory evaluation.
Includes bibliographical references and index.
Keywords: Food industry and trade; Food -- Microbiology; Food -- Quality control; Food handling; Nutrition